2019
DOI: 10.1371/journal.pone.0212351
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term fish predation destroys resilience of zooplankton communities and prevents recovery of phytoplankton control by zooplankton grazing

Abstract: Planktivorous fish predation directly affects zooplankton biomass, community and size structure, and may indirectly induce a trophic cascade to phytoplankton. However, it is not clear how quickly the zooplankton community structure and the cascading effects on phytoplankton recover to the unaffected state (i.e. resilience) once short-term predation by fish stops. The resilience has implications for the ecological quality and restoration measures in aquatic ecosystems. To assess the short-term zooplankton resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…Daphnia) while favouring small cladocerans (e.g. Bosmina, Chydorus), copepods, and rotifers (Ersoy, Brucet, Bartrons, & Mehner, 2019;Jakobsen, Hansen, Jeppesen, Grønkjaer, & Søndergaard, 2003). This is in line with our study where, small bodied zooplankton species, such as Bosmina longirostris, Dunhevedia sp.…”
Section: Effects Of Lhc On the Taxonomic And Trait Community Compossupporting
confidence: 92%
See 1 more Smart Citation
“…Daphnia) while favouring small cladocerans (e.g. Bosmina, Chydorus), copepods, and rotifers (Ersoy, Brucet, Bartrons, & Mehner, 2019;Jakobsen, Hansen, Jeppesen, Grønkjaer, & Søndergaard, 2003). This is in line with our study where, small bodied zooplankton species, such as Bosmina longirostris, Dunhevedia sp.…”
Section: Effects Of Lhc On the Taxonomic And Trait Community Compossupporting
confidence: 92%
“…are good swimmers, they are mostly restricted to fishless waters because their large body size and active behaviour also makes them highly sensitive to visual predation by fish (Kerfoot & Lynch, 1987;Nhiwatiwa et al, 2009). Bosmina, Chydorus), copepods, and rotifers (Ersoy, Brucet, Bartrons, & Mehner, 2019;Jakobsen, Hansen, Jeppesen, Grønkjaer, & Søndergaard, 2003). In this study, the large branchiopods were not observed in sites with high LHC.…”
Section: Effects Of Lhc On the Taxonomic And Trait Community Composmentioning
confidence: 50%
“…Co-evolution of zooplankton grazers to sizes that would allow them to ingest even the largest phytoplankton cells, colonies, and aggregates is strongly constrained as zooplankton themselves are on the menu of visually hunting predators (Lass & Spaak, 2003;Sommer et al, 2012). Even short-term fish predation events may lead to longer-term reduction in large-bodied grazers (Ersoy et al, 2019). Visually, hunting fish may induce several defenses in zooplankton too, such as Daphnia becoming smaller (Lass & Spaak, 2003), where smaller animals also have a lower maximum size of particles they can ingest (Burns, 1968).…”
Section: Consequences Of Phytoplankton Defenses For Population and Comentioning
confidence: 99%
“…It is commonly accepted that communities with higher species richness have an advantage in resource use efficiency (RUE, the amount of biomass produced per unit of supplied resource) [23,24] and this has also been shown for phytoplankton communities [25,26]. RUE often decrease with increasing grazing pressure on phytoplankton [27,28] and zooplankton grazing is another important factor determining the diversity and community structure of phytoplankton [29,30]. The biomass ratio of zooplankton to phytoplankton is a crude estimate of the zooplankton grazing pressure [31] and this ratio is also highest under mesotrophic conditions [22,32].…”
Section: Introductionmentioning
confidence: 99%